1993
DOI: 10.1190/1.1443465
|View full text |Cite
|
Sign up to set email alerts
|

A finite‐difference, time‐domain solution for three‐dimensional electromagnetic modeling

Abstract: An inhomogeneous Dirichlet boundary condition is imposed at the surface of the earth, while a homoge We have developed a finite-difference solution for neous Dirichlet condition is employed along the subsur three-dimensional (3-D) transient electromagnetic face boundaries. Numerical dispersion is alleviated by problems. The solution steps Maxwell's equations in using an adaptive algorithm that uses a fourth-order dif time using a staggered-grid technique. The time-step ference method at early times and a secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
160
0
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(169 citation statements)
references
References 32 publications
0
160
0
2
Order By: Relevance
“…The above formulation requires that the conductivity, dielectric permittivity and magnetic permeability be computed halfway along a given cell edge in Figure 1. Wang and Hohmann (1993) showed that an average conductivity (and pennitivity) can be evaluated by tracing out a line integral of the magnetic field centered on the midpoint of the cell edge. The resulting conductivity is simply a weighted sum of conductivities of the four adjoining cells.…”
Section: Numerical Solutionmentioning
confidence: 99%
“…The above formulation requires that the conductivity, dielectric permittivity and magnetic permeability be computed halfway along a given cell edge in Figure 1. Wang and Hohmann (1993) showed that an average conductivity (and pennitivity) can be evaluated by tracing out a line integral of the magnetic field centered on the midpoint of the cell edge. The resulting conductivity is simply a weighted sum of conductivities of the four adjoining cells.…”
Section: Numerical Solutionmentioning
confidence: 99%
“…The conductivities where the electric fields are located are represented by a weighted average of conductivities of the four adjoining cells based on Ampere's law (Wang and Hohmann, 1993;Alumbaugh et al, 1996).…”
Section: Appendix a Weighted Averaging Conduc-tivity And The Correspomentioning
confidence: 99%
“…To apply the boundary condition in 3-D, I use the upwardcontinuation scheme of Wang and Hohmann [32] to compute E 1 and E 2 above the surface using E 3 on the surface:…”
Section: Appendix C Air/water Boundary Conditionmentioning
confidence: 99%
“…Maaø [20] performed 3-D simulations with a FD method by using a mathematical transformation similar to the Kelvin-Voigt viscoelastic model. This model introduces a high permittivity as in the case of Wang and Hohmann [32]. Maaø [20] further reduced the computer time solving the equations in the high-frequency range by using a complexfrequency Fourier transform to filter high-frequency wave-like signals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation